This problem is on my summer packet for pre cal honors this year.
Write the following expression as a logarithm of a single quantity:
1/2[ln(x+1)+2ln(x-1)-3ln(2x+5)]+3lnx-2
I tried my best to solve it and ended up with this:
ln[(x+1)(x-1)^2(x^3)/(2x+5)^3]^1/2-2
I'm not sure if the two at the end can sit out like that. It would be great if someone can help =]
Distribute the throughout...
Use the power rule of logs...
Now apply the sum and difference properties of logs:
Now how do we bring the 2 into the logarithm?
We know that , thus .
Therefore, we now have:
Does this make sense?
I hope this clarifies things!!
--Chris
EDIT: Jhevon beat me...
Hi ,this is Kevin i had completed my Mathematics.and the concepts are very interested.This may be help full for the math students And for the young youth.And they may learn some knowledge from this forum.And i really appreciate for this thought.
================================================
Kevin00
Hookup Tonite